Effects of potassium channel knockdown on peripheral blood T lymphocytes and NFAT signaling pathway in Xinjiang Kazak patients with hypertension. (31st December 2023) - Dai, Chen; Tan, Meng; Meng, Xiaopan; Dong, Jian; Zhang, Yuanming
ABSTRACT: Backgroud and aim: T lymphocytes are involved in the occurrence and development of essential hypertension, and potassium channels are thought to be critical for lymphocyte activation. This study is to examine the roles of the voltage-gated potassium channels (Kv1.3) and calcium-activated potassium channels (KCa3.1) in peripheral blood T lymphocytes in Kazakh hypertensive patients of Xinjiang, China, mainly focusing on the effects of these channels on nuclear factor of activated T cells (NFAT) and inflammatory cytokines of T lymphocytes. Method: Kv1.3 and KCa3.1 gene silencing were performed in cultured T lymphocytes from Kazakh patients with severe hypertension. T cell proliferation after gene silencing was measured using CCK-8. The mRNA and protein expression levels were measured using RT-qPCR and Western blot analysis, respectively. Nuclear translocation of NFAT was observed using laser confocal fluorescence microscopy. Inflammatory cytokine levels were detected with ELISA. Results: Compared with control group, gene silencing of Kv1.3 and KCa3.1 respectively inhibited the proliferation of T cells. Moreover, compared with the control group, the mRNA expression levels of NFAT, IL-6 and IFN-γ were significantly decreased after gene silencing. Furthermore, the NFAT protein expression level was significantly down-regulated. In addition, the levels of IFN-γ and IL-6 in the cell culture supernatant were significantly decreased. Conclusion: Both Kv1.3 and KCa3.1 potassium channels activated T lymphocytes and enhanced the cytokine secretion possibly through CaN/NFAT signaling pathway, which may in turn induce micro-inflammatory responses and trigger the occurrence and progression of hypertension.